Small-bowel Metastasis from Gastric Sarcomatoid Carcinoma: A Case Report - Yu-Jen Chen; Hao Yen; Si-Yuan Wu (Journal of Medical Sciences)
Sarcomatoid carcinoma, distinguished by its histological presentation of undifferentiated, spindle-shaped cells, is a rare variant of gastric cancer when contrasted with the more typical adenocarcinoma. Gastric cancer rarely metastasizes to the small bowel; these cancers typically arise from breast, lung, or melanoma origins. Herein, we present the case of a 70-year-old male who experienced melena and significant weight loss over 3 months. An esophagogastroduodenoscopy revealed an extensive ulcerative lesion in the lower curvature of the high body of the stomach, which is consistent with the results of the computed tomography scans. Surgery involving total gastrectomy and resection of multiple segments of small-bowel tumors was conducted. Pathological examination confirmed the presence of sarcomatoid carcinoma with poorly differentiated adenocarcinoma, along with metastases to the small intestine. This report highlights the aggressiveness of gastric sarcomatoid carcinoma, as well as the potential for the small bowel to be a potential metastasis site.